Influence of Matrix Attachment Installation Load on Movement and Resultant Forces in Implant Overdentures. Issue 2 (27th June 2014) - Goto, Takaharu; Nagao, Kan; Ishida, Yuichi; Tomotake, Yoritoki; Ichikawa, Tetsuo
Abstract Purpose This in vitro study investigated the effect of attachment installation conditions on the load transfer and denture movements of implant overdentures, and aims to clarify the differences among the three types of attachments, namely ball, Locator, and magnet attachments. Materials and Methods Three types of attachments, namely ball, Locator, and magnetic attachments were used. An acrylic resin mandibular edentulous model with two implants placed in the bilateral canine regions and removable overdenture were prepared. The two implants and bilateral molar ridges were connected to three‐axis load‐cell transducers, and a universal testing machine was used to apply a 50 N vertical force to each site of the occlusal table in the first molar region. The denture movement was measured using a G2 motion sensor. Three installation conditions, namely, the application of 0, 50, and 100 N loads were used to install each attachment on the denture base. The load transfer and denture movement were then evaluated. Results The resultant force decreased with increasing installation load for all attachments. In particular, the resultant force on implants on the loading side of the Locator attachment significantly decreased when the installation load was increased from 0 to 50 N, and that for magnetic attachment significantly decreased when the installation load was increased from 50 to 100 N. For the residual ridges on the loading side, the direction of the forces for all attachments changed to downward with increasing installation load. Furthermore, the yaw Euler angle increased with increasing installation load for the magnetic attachment. Conclusions Subject to the limitations of this study, the use of any installation load greater than 0 N is recommended for the installation of ball and Locator attachments on a denture base. Regarding magnetic attachments, our results also recommend installation on a denture base using any installation load greater than 0 N, and suggest that the resultant force acting on the implant can be decreased by increasing the installation load; however, a large installation load of 100 N should be avoided when installing the attachment on the denture base to avoid increasing the denture movement.